2017
DOI: 10.1177/0269216317690685
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on Conducting and REporting DElphi Studies (CREDES) in palliative care: Recommendations based on a methodological systematic review

Abstract: Substantial variation was found concerning the quality of the study conduct and the transparency of reporting of Delphi studies used for the development of best practice guidance in palliative care. Since credibility of the resulting recommendations depends on the rigorous use of the Delphi technique, there is a need for consistency and quality both in the conduct and reporting of studies. To allow a critical appraisal of the methodology and the resulting guidance, a reporting standard for Conducting and REpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
1,161
2
24

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,098 publications
(1,192 citation statements)
references
References 67 publications
5
1,161
2
24
Order By: Relevance
“…Potential other pitfalls are, for example, imposing preconceptions of a problem and not allowing for the contribution of other related perspectives; poor techniques of summarizing and presenting the group responses; not exploring disagreements and; underestimating the demanding nature of a Delphi . A recent systematic review of reports based on the Delphi method found substantial variation in quality as consequence of lack of rigorousness of the application of the process . Ultimately the (new) standard terms are selected on the basis of arguments made transparent.…”
Section: Resultsmentioning
confidence: 99%
“…Potential other pitfalls are, for example, imposing preconceptions of a problem and not allowing for the contribution of other related perspectives; poor techniques of summarizing and presenting the group responses; not exploring disagreements and; underestimating the demanding nature of a Delphi . A recent systematic review of reports based on the Delphi method found substantial variation in quality as consequence of lack of rigorousness of the application of the process . Ultimately the (new) standard terms are selected on the basis of arguments made transparent.…”
Section: Resultsmentioning
confidence: 99%
“…The Delphi technique is increasingly becoming an important tool in establishing consensus to address issues in healthcare and health research . In our experience, we found the Delphi framework a simple but effective mechanism for facilitating agreement.…”
Section: Discussionmentioning
confidence: 99%
“…The Delphi technique is an iterative expert consultation and consensus building process that is accepted as relevant evidence in the field of health care and research . This paper follows the proposed standards for Guidance on Conducting and Reporting Delphi Studies (CREDES) …”
Section: Methodsmentioning
confidence: 99%
“…A Delphi study was conducted with 19 participants from 10 nursing colleges and nine hospitals to explore their altitude to the index system for the qualitative evaluation of undergraduate nursing student innovative ability. A modified recommendation for the Conducting and Reporting of Delphi studies (CREDES) was used to guide this study (Jünger, Payne, Brine, Radbruch, & Brearley, ) (see Appendix S1). A flow chart illustrating the Delphi process is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%